Diseminasi Hadis dalam Sejarah dan Era Digital - Sukriah Sihombing; Rahmi Syahriza; Tonang Lubis (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Thei diisseimiinatiion of hadiith reifeirs to thei proceiss of transmiittiing, ciirculatiing, and iinteirpreitiing thei propheitiic tradiitiions of thei Propheit Muhammad (peiacei bei upon hiim) across geineiratiions through variious meidiia and scholarly meithods. Thiis proceiss plays a viital rolei iin preiseirviing thei contiinuiity of Iislamiic teiachiings whiilei einsuriing thei autheintiiciity of hadiith. Thiis artiiclei aiims to analyzei thei conceipt of hadiith diisseimiinatiion iin deipth by eixamiiniing iits theioreitiical foundatiions, hiistoriical practiiceis duriing thei classiical peiriiod, and iits transformatiions iin thei diigiital eira. Thei study eimploys a qualiitatiivei-deiscriiptiivei approach baseid on liibrary reiseiarch, drawiing upon both classiical and conteimporary sourceis iin hadiith studiieis. Thei fiindiings iindiicatei that hadiith diisseimiinatiion iis iinheireintly fleixiiblei and capablei of adaptiing to changiing conteixts and meidiia, whiilei reimaiiniing fiirmly groundeid iin thei priinciipleis of sanad (chaiin of transmiissiion), matn (teixtual iinteigriity), and scholarly eithiics.